Low‐cycle fatigue behaviour of polyamides. Issue 11 (17th July 2015) - Şerban, D. A.; Marşavina, L.; Modler, N.; Wang, Q.; Palin‐Luc, T.
Abstract This work investigates a decrease in mechanical properties of a polyamide‐based polymer, previously subjected to low‐cycle fatigue tests in strain control. Variations in its tensile stress response under monotonic loading and instantaneous elastic modulus were studied in relation with three loading parameters of low‐cycle fatigue under strain control pre‐treatment, that is, number of cycles (5000, 10 000 and 50 000), frequency (3, 5 and 7 Hz) and reference strain (0.025, 0.035 and 0.045 mm mm−1; a constant amplitude of 0.0075 mm mm−1 was maintained). The tests (static and cyclic) were performed with a servo‐hydraulic testing machine Schenk PC63M equipped with a strain‐gauge extensometer. A significant softening in tensile stress response (32%) was observed after 1000 cycles with a decrease of 44% recorded after 50 000 cycles; the levels of frequency and the reference strain level within the test envelope have, instead, a small effect.